Family Firms, Audit Fee, and Auditor Choice: Evidence From Indonesia - Senny Harindahyani; Celine Widjaja (Master of Accounting Universitas Trunojoyo Madura, 2018)
Family firms in Indonesia have an important role in the Indonesian economy. However, agency problems might happen inside family firms where it will lead to conflict of interest and information asymmetry, along with the entrenchment effect where it leads firms to produce lower quality earnings report. Research from 305 firms in Indonesia shows that the agency problems and the entrenchment effect has not affected the family firms in Indonesia, reflected from the firm‟s decision making in their amount of audit fee and auditor choice. This study will contribute by providing an empirical evidence of the effect of family control on the audit fee and auditor choice in a developing country. The result shows that the type of firms has no correlation on the amount of audit fee paid to the auditor and both firms‟ demands the same level of audit quality where it is shown by their choices of audit firms, which is Big 4 audit firm or Non-Big 4 audit firm. In conclusion, the level of agency problems and entrenchment effect tends to be lower in the family firms of Indonesia.